The influence of post-exercise cold-water immersion on adaptive responses to exercise: A review of the literature - Broatch, J. R.; Petersen, A.; Bishop, D. J. (Sports Medicine, 2018)
Post-exercise cold-water immersion (CWI) is used extensively in exercise training as a means to minimise fatigue and expedite recovery between sessions. However, debate exists around its merit in long-term training regimens. While an improvement in recovery following a single session of exercise may improve subsequent training quality and stimulus, reports have emerged suggesting CWI may attenuate long-term adaptations to exercise training. Recent developments in the understanding of the molecular mechanisms governing the adaptive response to exercise in human skeletal muscle have provided potential mechanistic insight into the effects of CWI on training adaptations. Preliminary evidence suggests that CWI may blunt resistance signalling pathways following a single exercise session, as well as attenuate key long-term resistance training adaptations such as strength and muscle mass. Conversely, CWI may augment endurance signalling pathways and the expression of genes key to mitochondrial biogenesis following a single endurance exercise session, but have little to no effect on the content of proteins key to mitochondrial biogenesis following long-term endurance training. This review explores current evidence regarding the underlying molecular mechanisms by which CWI may alter cellular signalling and the long-term adaptive response to exercise in human skeletal muscle. Abstract from author